Manufacturing Execution System State-of-the-art: its evolution and dynamism focused on Industry 4.0 - Favela Camacho, Saúl Manuel; Molina Salazar, Javier; Rico, Lazaro (Springer, 2021)
The application of certain technologies, specifically information and communication technologies (ICT), in support of production processes, from top management to operational levels, is a trend that has increased throughout the time. Its use seeks support to functions like organization planning and management or controlling devices related with manufacturing processes. Likewise, the Manufacturing Execution System (MES) has become the bridge that connects enterprise resource planning systems with operations within organizations, becoming a “Digital Twin”, helping to know virtually what is happening on productive processes in real time. Like any practical concept, an updated state-of-the-art is needed to understand its evolution, importance level and dynamism, particularly nowadays when we are immersed in Industry 4.0 paradigm. This chapter will expose the outline of the state-of-the-art about MES, its implications in the manufacturing processes, and its transformation as productive systems change, in order to have a baseline in the design of new and related technologies.